AN ANALYSIS ON CHLOE MOVIE: A STUDY OF GENDER IDENTITY, SEXUAL ORIENTATION AND GENDER FLUIDITY - Listiana Ikawati (Equalita: Jurnal Studi Gender dan Anak, 2020)
The LGBT phenomenon is not a novel thing nowadays. Many controversies have arisen in response to whether it can be accepted or not. Some countries, especially Islamic countries including Indonesia insists that this is unacceptable because it violates the Islamic laws as stated in Quran and Hadith. Other countries, especially the western countries considered this to be normal and tolerable. The concern on this issue has also encouraged the actors in the movie industries to create some work representing how this phenomenon occurs. One of which is found in Chloe movie. This gender-related study aimed at analyzing how the gender identity, sexual orientation and gender fluidity were portrayed in the movie. It included how the main character perceive her gender identity and sexual orientation, why the gender fluidity existed and what reasons were underlying such behaviors. The analysis on the movie was carried out by using lesbian/ gay criticism. The result of the study shows that gender is a fluid entity. Admitting to belong to a particular gender identity requires someone to perform some roles which are agreed by the society. However, one’s gender identity does not always represent his or her sexual orientation. Some people even change their sexual orientation or gender fluidity. The movie reveals that heterosexual deprivation causes the gender fluidity. Lack of intimacy between husbands and wives may influence each of them to get the intimacy from people of the same gender. Last but not least, communication between husbands and wives plays a vital role to maintain the sexual relations that indirectly maintains the straightness of the gender identity and sexual orientation.